A determination of emergency department pre-triage times in patients not arriving by ambulance compared to widely used guideline recommendations. Issue 4 (5th December 2016) - Betz, Martin; Stempien, James; Trevidi, Sachin; Bryce, Rhonda
ABSTRACT: Objectives: Emergency department (ED) lengths of stay are measured from the time of patient registration or triage. The time that patients wait in line prior to registration and triage has not been well described. We sought to characterize pre-triage wait times and compare them to recommended physician response times, as per the Canadian Triage and Acuity Scale (CTAS). Methods: This observational study documented the time that consenting patients entered the ED and the time that they were formally registered and triaged. Participants' CTAS scores were collected from the electronic record. Patients arriving to the ED by ambulance were excluded. Results: A total of 536 participants were timed over 13 separate intervals. Of these, 11 left without being triaged. Participants who scored either CTAS 1 or 2 (n=53) waited a median time of 3.1 (interquartile range [IQR]: 0.43, 11.1) minutes. Patients triaged as CTAS 3 (n=187) waited a median of 11.4 (IQR: 1.6, 24.9) minutes, CTAS 4 (n=139) a median of 16.6 (IQR: 6.0, 29.7) minutes, and CTAS 5 (n=146) a median of 17.5 (IQR: 6.8, 37.3) minutes. Of patients subsequently categorized as CTAS 1 or 2, 20.8% waited longer than the recommended time-to-physician of 15 minutes to be triaged. Conclusions: All urban EDs closely follow patients' wait times, often stratified according to triage category, which are assumed to be time-stamped upon a patient's arrival in the ED. We note that pre-triage times exceed the CTAS recommended time-to-physician in a possibly significant proportion of patients. EDs should consider documenting times to treatment from the moment of patient arrival rather than registration. RÉSUMÉ: Introduction: La durée du séjour (DS) au service des urgences (SU) se mesure depuis le moment de l'inscription ou celui du triage. Toutefois, le délai d'attente écoulé avant l'inscription ou le triage est mal connu. Aussi les auteurs ont-ils cherché à caractériser le délai d'attente avant le triage et à le comparer avec le délai pour l'évaluation initiale par le médecin, recommandé dans l'Échelle canadienne de triage et de gravité (ECTG). Méthode: Il s'agit d'une étude d'observation dans laquelle ont été recueillies des données sur le délai d'attente des patients qui sont arrivés au SU et qui ont accepté de participer à l'étude, et sur le délai d'attente avant qu'ils soient officiellement inscrits et triés. Les cotes de priorité relatives à l'ECTG ont été recueillies à l'aide des dossiers électroniques. Les patients qui sont arrivés au SU en ambulance ont été exclus. Résultats: A été mesuré le délai d'attente de 536 participants sur 13 périodes distinctes. Sur ce nombre, 11 malades sont partis sans avoir été triés. Le délai d'attente médian chez les participants qui avaient reçu une cote 1 ou 2 selon l'ECTG (n=53) était de 3, 1 minutes (écart interquartile [EI] : 0, 43 - 11, 1). Quant au délai d'attente médian chez les participants qui avaient reçu une cote 3 (n=187), il était de 11, 4 minutes (EI : 1, 6 - 24, 9); chez ceux qui avaient reçu une cote 4 (n=139), il était de 16, 6 minutes (EI : 6, 0 - 29, 7) et chez ceux qui avaient reçu une cote 5 (n=146), il était de 17, 5 minutes (EI : 6, 8 - 37, 3). Enfin, 20, 8 % des patients ayant reçu ultérieurement une cote 1 ou 2 selon l'ECTG ont attendu plus longtemps que le délai recommandé de 15 minutes pour l'évaluation initiale par un médecin avant d'être triés. Conclusions: Les délais d'attente, qui sont souvent répartis selon la cote de priorité et que l'on suppose horodatés à l'arrivée des patients, font l'objet d'un suivi étroit dans tous les SU urbains. Les auteurs ont toutefois relevé que les délais d'attente avant le triage dépassaient le délai recommandé pour l'évaluation initiale par un médecin selon l'ECTG, et ce, dans une proportion vraisemblablement importante de patients. Aussi les SU devraient-ils calculer le temps écoulé avant le traitement depuis l'arrivée des patients plutôt que depuis leur inscription.